The effect of radiation on The Antibacterial Activity of Allicen - Khalid K. Al-Bayatti (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2010)
It is known that garlic cloves had antibacterial action on a wide range of microorganisms both g (+) and g (-) bacteria. The antibacterial activity of garlic is mainly attributed to allicin, the active principle of this vegetable. The antibacterial activity of allicin is inhibited by different chemical and physical agents. No studies were available to elustrate the effect of ionizing radiation on the activity of this compound. Allicin was water extracted according to ALDelamy, and different concentrations of this extract were irradiated with different doses of gamma-radiation from γ-cell 20. The results obtained indicated that doses of radiation up of 3 megarad did not affect the antibacterial activity of allicin, whereas higher doses, 5 megarad and up, will inhibit the activity completely. We conclude from these results that higher doses of radiation should not be used for preservation of garlic cloves because of its inhibitory effect on the active principle of garlic, allicin.